2021
DOI: 10.1016/j.immuni.2021.11.001
|View full text |Cite|
|
Sign up to set email alerts
|

Lipid nanoparticles enhance the efficacy of mRNA and protein subunit vaccines by inducing robust T follicular helper cell and humoral responses

Abstract: Adjuvants are critical for improving the quality and magnitude of adaptive immune responses to vaccination. Lipid nanoparticle (LNP)-encapsulated nucleoside-modified mRNA vaccines have shown great efficacy against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), but the mechanism of action of this vaccine platform is not well-characterized. Using influenza virus and SARS-CoV-2 mRNA and protein subunit vaccines, we demonstrated that our LNP formulation has intrinsic adjuvant activity that promotes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
302
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 395 publications
(320 citation statements)
references
References 88 publications
(119 reference statements)
14
302
2
2
Order By: Relevance
“…A probable explanation for this difference is that, unlike mono-epitope systems, in the case of a poly-epitope system, some clones keep expanding in the late GC reaction, thereby also generating memory B cells at later time point. Furthermore, this study showed that, like in the case of flavivirus-specific memory B cell generation ( 37 ), B cells with low affinity germline BCRs are prone to be selected into memory B cells. Given that the germline BCR of bnAbs usually has very low affinity for the native antigens of influenza virus, this may be one of the reasons why broadly reactive clones against influenza virus can exist in the memory fraction ( 38 ).…”
Section: Gc Responsesmentioning
confidence: 86%
See 1 more Smart Citation
“…A probable explanation for this difference is that, unlike mono-epitope systems, in the case of a poly-epitope system, some clones keep expanding in the late GC reaction, thereby also generating memory B cells at later time point. Furthermore, this study showed that, like in the case of flavivirus-specific memory B cell generation ( 37 ), B cells with low affinity germline BCRs are prone to be selected into memory B cells. Given that the germline BCR of bnAbs usually has very low affinity for the native antigens of influenza virus, this may be one of the reasons why broadly reactive clones against influenza virus can exist in the memory fraction ( 38 ).…”
Section: Gc Responsesmentioning
confidence: 86%
“…In addition to antigen, development of good adjuvants for inducing Tfh cells is also important. Indeed, lipid nanoparticles used for mRNA vaccines have recently been shown to facilitate Tfh cell generation, presumably through enhancing IL-6 production ( 37 ).…”
Section: Generation Of Broadly-neutralizing Memory B Cells and Their Recallmentioning
confidence: 99%
“…Intramuscular and intradermal administration of mRNA vaccines is highly immunogenic and induces local cytokine and chemokine production that initiates prompt recruitment of neutrophils, monocytes, and other cells to prime the immune response/s. Injection of mRNA encapsulated in lipid nanoparticles (mRNA-LNP) has been shown to induce robust infiltration of neutrophils, monocytes, and dendritic cells as well as the activation of pro-inflammatory cytokines (e.g., IL-1β, PTX3, NLRP3, IL-6, GM-CSF) and chemokines (e.g., CXCL-10, CXCL-11, MIP-2) in mice and rhesus macaques [160][161][162]. In contrast to synDNA, mRNA vaccines are directly translated in the cytoplasm, and the ensuing proteins are processed and presented on MHC-I and II, followed by the presentation to CD8 + T cells and CD4 + T helper cells in the draining lymph nodes (Figure 2).…”
Section: Mrna Based Vaccinesmentioning
confidence: 99%
“…In this issue of Immunity , Alameh et al. demonstrate that LNPs act as potent adjuvants, enhancing T follicular helper (Tfh) cells, germinal center B (GCB) cells, long-lived plasma cells (LLPCs), and memory B (MB) cells associated with protective and durable Ab responses ( Alameh et al., 2021 ). Remarkably, these LNPs optimized for mRNA delivery are also potent adjuvants for protein antigens (recombinant influenza HA [rHA] and recombinant receptor binding domain [rRBD] of SARS-CoV-2 spike), highlighting their potential for both RNA and subunit protein antigens.…”
Section: Main Textmentioning
confidence: 99%
“… Adjuvants can be incorporated into vaccines to enhance the magnitude and functionality of adaptive immune responses. In this issue of Immunity , Alameh et al. (2021) reveal that lipid nanoparticles, which are key components of effective SARS-CoV-2 mRNA vaccines, have broad adjuvant function, enhancing B cell responses and protective efficacy of protein-based subunit in addition to mRNA antigens.…”
mentioning
confidence: 99%